Effects of long-term intensive training in teenage male wrestlers aged between 12 to 14 years - Çiplak, M. E.; Yamaner, E.; Imamoglu, O.; Yamaner, F. (International Journal of Applied Exercise Physiology, 2020)
The aim of the study was to investigate the effects of long-term intensive training on biochemical blood parameters of teenage male wrestlers. Material and Methods: 32 healthy boys (12.93±0.25) were grouped as athletes (A) and control (C). The athlete group joined an intensive training program with a controlled diet for 8 months, whereas control group did not receive any training or diet. Pre-posttest results were analyzed with Paired sample t test and Mann Whitney U test by SPSS 15.0. Development of athletes and control group were alike in terms of height, weight and BMI. Glucose and insulin serum levels decreased in the athlete group, whereas leptin serum levels did not differ among groups in pretest and posttest results. There were no significant differences between pretest and posttest results in terms of cholesterol, triglyceride, creatine and LDL levels, whereas HDL levels (p=0.05) were decreased in the athlete group after 8 months training period. Statistically significant increase was observed in uric acid, phosphorus serum levels and platelets (p<0.01) in athlete group. It was concluded that the low-fat diet together with intense training program caused decreased HDL levels and increased uric acid levels in serum which may serve as biomarkers for cardiovascular disease. The intense training program did not cause any muscle damage since creatine levels were not altered but increase in uric acid levels and phosphorus in serum were explained with high oxidative stress as a result of training.